THE INFLUENCE OF JOB SATISFACTION, ORGANIZATIONAL COMMITMENT AND CAREER DEVELOPMENT ON TURNOVER INTENTION AT PT BANK MESTIKA DHARMA, TBK PEKANBARU - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 5 No 2 (2025): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to determine the effect of job satisfaction, organizational commitment and career development on employee Turnover Intention of PT Bank Mestika Dharma, Tbk Pekanbaru. This study uses Multiple Linear Regression with descriptive and linear analysis methods using the SPSS Version 21 application. The sample in this study were all permanent employees who worked at PT Bank Mestika Dharma, Tbk Pekanbaru totaling 40 people. The sampling technique in this study used the saturated sampling method or census because the population studied was less than 100 people. The data collection method used a questionnaire distributed to respondents. The results of the study explain that job satisfaction and organizational commitment have a positive effect on Turnover Intention at PT. Bank Mestika Dharma, Tbk Pekanbaru, while career development has a negative effect on Turnover Intention at PT. Bank Mestika Dharma, Tbk Pekanbaru. It is recommended to the company to be able to further improve Human Resources and also need to carry out company activities outside of working hours that can increase Organizational Loyalty to foster feelings of attachment, and devotion to the company.